FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK (TAX AVOIDANCE) DI PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012 SD 2016 - Tommy Ferdian (Yayasan Akrab Pekanbaru, 2019)
The purpose of this research is to find out the factors that affect Tax Avoidance in Mining Companies listed on the Indonesia Stock Exchange in 2012 to 2016, these factors are limited by audit committees, audit quality, profitability and capital intensity. The results show that the audit committee partially has no effect on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange in 2012-2016. Audit quality partially does not affect tax avoidance in mining sector companies listed on the Indonesia Stock Exchange in 2012-2016. Profitability partially has a significant effect on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange in 2012-2016. Capital intensity partially does not affect tax avoidance in mining sector companies listed on the Indonesia Stock Exchange in 2012-2016. Based on the simultaneous significant test results (Statistical Test f) so that the results of the study show that corporate governance (which is proxied by the audit committee and audit quality), profitability and capital intensity simultaneously have a significant effect on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange in the year 2012-2016